Impact of post-harvest storage conditions on polyphenol composition and antioxidant activity in natural almonds - Ragno, Agnese; Imbesi, Martina; Gervasi, Teresa; Smeriglio, Antonella; Mandalari, Giuseppina; Impellizzeri, Daniela; Trombetta, Domenico (Frontiers in Nutrition, 2025)
BackgroundPost-harvest storage of natural almonds is a critical step, as it can cause the onset of microbial contamination and modify polyphenolic composition of almond skin, potentially altering the antioxidant capacity and overall, the health effects of the native product. This study aims to evaluate the impact of different post-harvest storage conditions on the microbiological stability, polyphenolic profile, and antioxidant activity of natural almonds (Prunus dulcis cv. “Fascionello”).MethodsNatural almonds were obtained from Consorzio Mandorla di Avola and stored under three conditions: light exposure at room temperature (RT), dark at RT, and dark at 4°C, monitoring temperature and relative humidity. Samples were analyzed at four time points (T0, T3, T6, and T9 months). Microbiological stability was assessed using standard plate-counting techniques; polyphenolic content was determined through spectrophotometric assays and RP-LC-DAD-ESI-MS/MS analysis, whereas the antioxidant activity was evaluated using different spectrophotometric and spectrofluorimetric assays including DPPH, TEAC, FRAP, and ORAC assays. Chemometric analyses were performed to compare polyphenolic changes across different storage conditions over time.ResultsTemperature remained stable with moderate variations, indicating a well-controlled environment, while humidity exhibits significant fluctuations, likely influenced by external factors. No significant microbial contamination was detected throughout storage, confirming the microbiological safety of natural almonds. The polyphenolic content significantly decreased within the first 3 months, particularly under dark conditions at RT. However, a recovery phase was observed at 6 months, with cold-stored almonds retaining the highest levels of total polyphenols and flavonoids. The antioxidant activity of almond skin extracts correlated with polyphenolic content, showing an initial decline followed by stabilization under refrigerated storage. Hierarchical clustering analyses highlighted distinct polyphenolic expression patterns based on storage conditions and time points.ConclusionPost-harvest storage conditions significantly impact the polyphenolic profile and antioxidant properties of natural almonds. For short-term storage (≤6 months), RT with controlled light exposure is sufficient to preserve polyphenols, whereas cold and dark conditions are recommended to maintain bioactive compound stability and antioxidant potential for long-term storage (>6 months). These findings provide valuable insights for optimizing storage strategies in the food, nutraceutical, and pharmaceutical industries.